Recovery and sustainable use of the Chorrillos beach of Huacho, Peru. (LACCEI, 2024)
This article shows the environmental recovery and sustainable use of the Chorrillos of Huacho beach, which is polluted and closed but it is recoverable according to Jáuregui [1]. In spite of being contaminated, the competent authorities and the population do not act for this recovery and its use, moreover, they are aware that this environment affects their health and their economy, and due to the lack of opportunities the population migrates. Therefore, it is essential the environmental recovery of this beach and its use as a great opportunity for human development, for it was evaluated the environmental opportunities it offers, as well as other resources that exist in the area, allowing it to be more attractive for tourism. For this, references have been taken among other experiences published by the United Nations (UN) and other documentary means, which have allowed making proposals for environmental management and sustainable use of this beach, as well as its measurement of sustainability indicators of Pressure-State-Response (PER), which shows that it is possible to apply these proposals and whose experience is also a contribution for the sustainable development of other towns in a similar situation.